Ancient DNA sequence quality is independent of fish bone weight. (January 2023) - Atmore, Lane M.; Ferrari, Giada; Martínez-García, Lourdes; van der Jagt, Inge; Blevis, Rachel; Granado, José; Häberle, Simone; Dierickx, Katrien; Quinlan, Liz M.; Lõugas, Lembi; Makowiecki, Daniel; Hufthammer, Anne Karin; et al.
Abstract: The field of ancient DNA (aDNA) typically uses between 50 and 200 mg of minimum input weight of bone material for the extraction of DNA from archaeological remains. While laboratory and analysis techniques have focused on improved efficiency of extracting useable sequence data from older and poorer quality remains, bone material input requirements have rarely been critically evaluated. Here, we present the aDNA analysis of 121 size-constrained Atlantic herring remains – weighing between <10 and 70 mg – that were individually sequenced to explore the capacity of successful aDNA retrieval from small archaeological remains. We statistically evaluate the relationship between bone weight and several response variables, including library success, endogenous DNA content, and library complexity, i.e., the number of unique molecules that are obtained. Remarkably, we find no relationship between bone weight and library success, levels of endogenous DNA, or library complexity. Our results imply that – at least in the case of fish bone – even minute bones can yield positive results and that the presumed minimum sample size required should be re-evaluated. Archaeological site, instead of bone size, is the primary driver of DNA sequence quality. Our work expands the number of specimens considered suitable for aDNA analyses, and therefore facilitates efforts to minimize the destructive impact of aDNA research and mediate some of the ethical concerns surrounding destructive analysis. Highlights: Whole-genome ancient DNA (aDNA) sequences have been successfully recovered from bones weighing less than 10 mg. ADNA sequence quality is not significantly associated with starting bone weight. Using small amounts of bone material can mitigate some ethical issues posed by destructive sampling. Researchers should interrogate the amount of material and species investigated for aDNA research.